ImiFlex Rates for Efficacy in Imidazolinone-Tolerant Grain Sorghum - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2022)
The objective of this study was to compare ImiFlex rates and timings for efficacy and crop response in imidazolinone-tolerant grain sorghum. Volunteer corn and Johnsongrass control was generally best when ImiFlex (imazamox) was applied postemergence (POST), except when tank mixed with Huskie (bromoxynil/pyrasulfotole). Likewise, Palmer amaranth control was most consistent when ImiFlex was applied POST. Though all herbicides increased grain yields relative to the weedy controls, yields increased the most when Moccasin II Plus (metolachlor) plus Motif (mesotrione) preemergence (PRE) was followed by ImiFlex POST or Moccasin II Plus and Sharpen (saflufenacil) PRE was followed by ImiFlex plus atrazine POST.
Keywords: Imidazolinone-resistant sorghum; Igrowth sorghum